2022
DOI: 10.3329/taj.v35i1.61159
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Screening to Evaluate the Status of Newborn Hearing Impairment in the NICU of a Tertiary Hospital

Abstract: Introduction: One to three per 1,000 live births suffers from significant hearing impairment. However, 2 to 4 per 100 infants who survived neonatal intensive care have some degree of sensorineural hearing loss. If hearing impairment in newborns is detected earlier, early management can prevent undesirable and often irreversible damage due to late detection.  Early detection and the treatment of hearing impairment in children are essential for the development of communication skills, social skills, emotional we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sixteen studies that reported a two-stage hearing screening protocol, employed OAE (TE/DP-OAE) or AABR as screening tests (individually or combined in either stage) 17–31. The other 25 studies used only OAEs (DP/TE)32–49 or AABR screening50 51 for testing in both stages. Those studies that reported the use of AABR in the initial stage of screening either employed AABR solely for both stages50 or a combination of AABR and OAE to screen only high-risk newborns 20 52.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies that reported a two-stage hearing screening protocol, employed OAE (TE/DP-OAE) or AABR as screening tests (individually or combined in either stage) 17–31. The other 25 studies used only OAEs (DP/TE)32–49 or AABR screening50 51 for testing in both stages. Those studies that reported the use of AABR in the initial stage of screening either employed AABR solely for both stages50 or a combination of AABR and OAE to screen only high-risk newborns 20 52.…”
Section: Resultsmentioning
confidence: 99%
“…Diagnostic ABR was the only testing carried out to confirm the hearing loss in studies in newborns and infants 25 28 32 35–37 42 54 63 86–89. Comprehensive test battery including the diagnostic BERA, OAE, and tympanometry was mentioned only in 11 studies 20 29 58.…”
Section: Resultsmentioning
confidence: 99%